MRI Features in a Rat Model of H-ABC Tubulinopathy - Garduno-Robles, Angeles; Alata, Milvia; Piazza, Valeria; Cortes, Carmen; Eguibar, Jose R.; Pantano, Sergio; Hernandez, Victor H. (Frontiers in Neuroscience, 2020)
Tubulinopathies are a group of recently described diseases characterized by mutations in the tubulin genes. Mutations in TUBB4A produce diseases such as dystonia 4 (DYT4) and hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC), which are clinically diagnosed by magnetic resonance imaging (MRI). We propose the taiep rat as the first animal model for tubulinopathies. The spontaneous mutant suffers from a syndrome related to a central leukodistrophy and characterized by tremor, ataxia, immobility, epilepsy and paralysis. The clinical signs presented by these rats and the morphological changes we found by our longitudinal MRI study are similar to those of patients with mutations in TUBB4A. The diffuse atrophy we found in brain, cerebellum and spinal cord is related to the changes detectable in many human tubulinopathies and in particular in H-ABC patients, where myelin degeneration at the level of putamen and cerebellum is a clinical trademark of the disease. We performed Tubb4a exon analysis to corroborate the genetic defect and formulated hypotheses about the effect of aminoacid 302 change on protein physiology. Optical microscopy of taiep rat cerebella and spinal cord confirmed the optical density loss in white matter associated with myelin loss, despite the persistence of neural fibers.